Pemantauan Limbah Industri Tahun 2020-2022 Menggunakan Google Earth Engine Di Perairan Pengambengan, Kabupaten Jembrana - Amalia Rachmawati Sukamto; Yuswanti Ariani Wirahayu (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
These industrial activities produce waste that has the potential to pollute waters, which has a negative impact on the environment and public health. One type of water pollution is Total Suspended Solid (TSS) with the number of undissolved particles measuring less than 0.004 mm to 1 mm. The purpose of this study is to determine and analyze the level of industrial waste pollution in Pengambengan Waters in 2020 to 2022 using Google Earth Engine. The method used in analyzing data uses the Google Earth Engine platform with sentinel-2 imagery, then in obtaining total suspended solid results using the Laili (2015) algorithm conducted in a case study of Poteran Waters, East Java. The results of industrial waste monitoring can be seen that the miminal suspension results in Pengambengan Waters are 16.1296 mg/L to a maximum of 20 mg/L while in the second class, the total suspended solid reaches 22.0348 mg/L from a maximum total of 40 mg/L. This suspension result is still relatively low due to the classification class only reaching class two. The absence of areas that fall into class 3 and above indicates that the level of pollution has not reached critical levels.